Elementary English Language Instruction : Colombian Teachers’ Classroom Practices (2004)
ABSTRACT: An in-progress ethnographic research project about teachers who are facing the complex task of teaching English to children in 7 public elementary schools in the metropolitan area of Medellin is presented in this article. First, the need for this research is outlined by researchers; second, the methodology of the project is described; third, up-to-date findings which include a profile of the 12 teachers who are participating in this study, and an analysis of their class methodology in terms of activities, materials, teacher and student roles are reported. Lastly, implications of this research project related to early foreign language instruction are highlighted.